The prediction of wood properties from anatomical characteristics: the case of common commercial Malaysian timbers - Toong, Weiching; Ratnasingam, Jegatheswaran; Mohamad Kasim, Mohamad Roslan; Halis, Rasmina (North Carolina State University, 2014)
This study established a predictive relationship between the material properties and the anatomical characteristics of common commercial Malaysian timbers. Anatomical databases were analysed using a one-way analysis of variance (ANOVA), a Duncan test, and the Spearman and Pearson correlation tests, and then modelled using multiple regression (stepwise method with constant excluded). The correlation tests revealed that the properties and anatomical characteristics of the wood were strongly correlated. The predictability of the resulting equation models was quite high. The equation models were able to relate various anatomical characteristics to wood texture, porosity, density, radial shrinkage, modulus of elasticity, and compression parallel to grain. This finding suggests that the relationship between the properties and the anatomical characteristics of wood can be described successfully using multiple regression equation models.